From Daily Need Experiences to Autonomy-Supportive and Psychologically Controlling Parenting via Psychological Availability and Stress. (3rd July 2019) - Van Der Kaap-Deeder, Jolene; Soenens, Bart; Mabbe, Elien; Dieleman, Lisa; Mouratidis, Athanasios; Campbell, Rachel; Vansteenkiste, Maarten
SYNOPSIS: Objective. This study sought to identify processes linking daily parental need experiences to daily parenting, focusing on the intervening role of parental psychological availability and stress. Design. In total, 206 mothers ( M age = 40.33 years) and 206 fathers ( M age = 42.36 years) and their elementary school child ( M age = 9.93 years; 46.6% female) participated in a 7-day multi-informant diary study. Results. Parents' daily need satisfaction was related to more daily psychological availability and lower daily stress in parent-child interactions, but parental need frustration related to less daily psychological availability and more stress. Psychological availability and stress were related to more daily parent-reported and child-perceived autonomy support and psychological control, respectively. However, parental need-based experiences were related to children's reported parenting only indirectly (i.e., through psychological availability and stress). These associations were obtained at the within-day level but not in models predicting parenting the next day. Conclusion. Parental need-based experiences are a critical resource for parenting.